Serum Vitamin D Level in Children with Type 1 diabetes mellitus in Duhok city, Iraq - Haleem, Azad A. (Science Journal of University of Zakho, 2019)
Type 1 Diabetes Mellitus is an autoimmune disorder that occurs in the Β-cells of pancreatic islets. Vitamin D is essential in maintaining the bone health. It has proven that Vitamin D has an autoimmune disorders including T1DM. Hence, the aim is to detect the prevalence of vitamin D deficiency among children with T1DM. A case control study conducted in Duhok, North of Iraq between 15th of February and 15th of August 2016. 100 enrolled participants aged from 5 to 15 years of both genders were divided in to two groups. Fifty of them had T1DM and 50 children who were healthy and non-diabetic. All participants were studied in terms of age, gender, duration of diabetes, glycemic control (HbA1c) and Body Mass index .Samples of blood were taken to measure serum Vitamin D and HbA1c levels. Mean serum Vitamin D level in diabetic group was 6.068 ±2.45 ng/mL while in the control group it was 21.101 ±9.23 ng/mL. Vitamin D were lower in the diabetic patients than controls (P= 0.01). Vitamin D level was indirectly correlated with duration of diabetes (P=0.01).Level of Vitamin D was decreased with increasing HbA1C (P=0.01). Level of Vitamin D was not significantly related to body mass index. Vitamin D level is not significantly related to body mass index.
Keywords: Vitamin D; Children; Type 1 diabetes mellitus; Duhok